DI/TII SULAWESI-SELATAN: POLITIK EKONOMI DI TENGAH KONFLIK 1953-1959 - Ahmad Subair (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This study specifically discusses economic political developments in the time of movement in southern DI/TII in South Sulawesi 1953-1959.The safety of the security measures taken in South Sulawesi in the time of the guerrilla crisis, and continue during the time of its true armed confrontation is not yet clear. There are some things that escape the historian related to the events of the DI/TII in South Sulawesi, especially the political political symptoms that influence the course of historical flow. The events of the DI/TII that took place so long are finally remembered as memories of a mere age. The label of the label and the other has become a typical character in view of the event in the DI/TII South Sulawesi. In small moments such us can be given the meaning of the symptoms of the movement/factor can grow and endure. It is actually a little bit as obscure as a survival factor in the movements of the DI/TII in South Sulawesi. Like DI / TII's marketing, it builds economic power to fund its weaponry. The movements of the DI/TII in the old are an accumulation of small events occurring everywhere, and a simultaneous accident. A small event falls to the object of this study. Especially small events that affect the leader and grassroots action in the DI/TII. The author sees the object of the study as a factor that speeds up an act of actor even the movement of the people. In the end the state can see and read the situation that is being played by DI/TII. The results can be seen in the technical policies played by the Army and entered into total isolation policies against the movement of DI/TII in South Sulawesi.